2013
DOI: 10.1371/journal.pone.0069255
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Characterization of a Novel Carlavirus Infecting Potatoes in China

Abstract: A new carlavirus, tentatively named Potato virus H (PVH), was found on potato plants with mild symptoms in Hohhot, Inner Mongolia Autonomous Region, China. PVH was confirmed by genome sequencing, serological reactions, electron microscopy, and host index assays. The PVH particles were filamentous and slightly curved, with a modal length of 570 nm. Complete RNA genomic sequences of two isolates of PVH were determined using reverse transcription-PCR (RT-PCR) and the 5′ rapid amplification of cDNA ends (5' RACE) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 37 publications
(39 reference statements)
1
23
0
Order By: Relevance
“…The lack of association of isolate variation with geographic location highlights the world-wide movement of potato germplasm. Similar results have been reported for PVS [2,16], PVM [18,21], PVP [6] and Hop mosaic virus (HpMV) [15].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The lack of association of isolate variation with geographic location highlights the world-wide movement of potato germplasm. Similar results have been reported for PVS [2,16], PVM [18,21], PVP [6] and Hop mosaic virus (HpMV) [15].…”
Section: Discussionsupporting
confidence: 83%
“…To date, Potato virus S (PVS), Potato virus H (PVH), Potato latent virus (PotLV), Potato virus P (PVP) and PVM are known carlaviruses reported to infect potato plants naturally worldwide [4,6,10,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PYMV is considered rare in potato (Geraud-Pouey et al, 2016) and reported to incidentally infect potato plants that grow in the vicinity of infected tomato crops . Might cause symptoms under specific conditions (particular varieties, mixed infections) PVH Yes Not evaluated Yes Two reports in potato, one indicating mild leaf symptoms (Li et al, 2013). Therefore, no impact is expected on potato or other hosts in the EU territory.…”
Section: Rnqpsmentioning
confidence: 99%
“…: IIIA 10,11,12; IVAI 25.Additional experimental Solanaceous hosts are reported(Li et al, 2013). Data regarding natural hosts were retrieved from the EPPO global database and CABI crop protection compendium (CABI cpc) up to 30-4-2019 and if different source used specified in the table Narrow host range reported, additional natural hosts may exist Nicotiana sp.…”
mentioning
confidence: 99%